2020
DOI: 10.1002/app.48956
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioresource‐based poly(3‐Hydroxybutyrate‐co‐4‐Hydroxybutyrate)/poly(LacticAcid) blend fibers with high strength and toughness via melt‐spinning

Abstract: Novel biodegradable blend fibers based on the biomaterials poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB) and poly(lacticacid) (PLA) were successfully prepared by combining melt spinning and hot drawing. The results showed that the commixture could continuous and stable spin for a P3HB4HB ratio of 30-35 wt% and winding speed of 20-30 m/min. The thermal stability of the P3HB4HB/PLA blend fiber was increased, as determined by thermogravimetric analysis. The crystallinity degree of the P3HB4HB/ PLA blend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Neat P(3HB)(4HB) film sample features only Tg and unclear melting point, indicating that the P(3HB)(4HB) film samples were indeed in amorphous state as observed in other studies 11,17,28 …”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Neat P(3HB)(4HB) film sample features only Tg and unclear melting point, indicating that the P(3HB)(4HB) film samples were indeed in amorphous state as observed in other studies 11,17,28 …”
Section: Resultssupporting
confidence: 65%
“…The XRD scans of P(3HB)(4HB)/PLA cast films are presented in Figure 10. The diffraction peaks registered in the XRD analysis of CL blends are the following; 13.8°, 16.9°, 27.5°, and 29.1° associated with planes (020) for P(3HB)(4HB), (110) for PLA and P(3HB)(4HB), (040) and (002) for P(3HB)(4HB), respectively 28,42,43 . The results show that CL 10 exhibited only a slightly hinted peak located at 17° associated to (110) planes of PLA 43 .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…29 To further tailor and improve the crystallinity of PLLA, it is necessary to obtain an in-depth understanding on the true mechanism of nucleation and growth of PLLA in the PLLA/PHAs blends. It has been frequently reported that the PHAs phases in the PLLA/PHAs blends served as nucleating agents to accelerate the overall crystallization of PLLA, such as PHB, 30,31 P34HB, 32 and PHBV. [33][34][35] Besides, the PHAs phases including PHB and P34HB were found to act as spherulite growth-accelerating or plasticizing agents, enhancing the crystallization of PLLA.…”
mentioning
confidence: 99%